Analytical seismic assessment of RC dual wall/frame systems using SLaMA: Proposal and validation. (1st June 2019) - Gentile, Roberto; Pampanin, Stefano; Raffaele, Domenico; Uva, Giuseppina
Highlights: A by-hand procedure for the non-linear capacity curve of RC wall/frame systems is proposed. The mechanical interaction among frame(s) and wall(s) is explicitly considered. 28 case studies: different geometry, wall-to-frame strength ratio and plastic mechanism. Comparison with pushover analyses shows a maximum 5% error (base shear and displacement). Abstract: A paramount step in seismic assessment of existing structures is the determination of the structural capacity. It is widely recognised that non-linear numerical approaches are arguably the most reliable tool to achieve this goal. However, reliable yet simple analytical procedures are needed to identify potential structural weaknesses and their influence on the overall capacity, to cross-check and/or interpret numerical analyses. This paper presents a novel analytical -or "by-hand"- procedure to calculate the non-linear capacity curve of RC dual wall/frame systems within the framework of the Simple Lateral Mechanism Analysis (SLaMA). The mechanical interaction among frame(s) and wall(s) is explicitly considered to calculate their base shear and overturning moment contributions. The procedure is outlined and applied to 28 case studies with different geometry, wall(s) position, wall-to-frame strength ratio and plastic mechanism. The results are compared to refined numerical pushover analyses, showing a maximum 5% error both in terms of ultimate base shear and displacement for the majority of the case studies.